2015
DOI: 10.1128/jcm.02930-14
|View full text |Cite
|
Sign up to set email alerts
|

Differential Single Nucleotide Polymorphism-Based Analysis of an Outbreak Caused by Salmonella enterica Serovar Manhattan Reveals Epidemiological Details Missed by Standard Pulsed-Field Gel Electrophoresis

Abstract: We retrospectively analyzed a rare Salmonella enterica serovar Manhattan outbreak that occurred in Italy in 2009 to evaluate the potential of new genomic tools based on differential single nucleotide polymorphism (SNP) analysis in comparison with the gold standard genotyping method, pulsed-field gel electrophoresis. A total of 39 isolates were analyzed from patients (n ‫؍‬ 15) and food, feed, animal, and environmental sources (n ‫؍‬ 24), resulting in five different pulsed-field gel electrophoresis (PFGE) profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…1 ). A number of studies have reported the use of SNP-based analysis as a potential molecular subtyping tool for outbreak investigation in multiple Salmonella serovars including Dublin [ 29 ], Enteritidis [ 22 , 30 ], Heidelberg [ 31 ], Manhattan [ 21 ], Montevideo [ 32 , 33 ], and Typhimurium [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). A number of studies have reported the use of SNP-based analysis as a potential molecular subtyping tool for outbreak investigation in multiple Salmonella serovars including Dublin [ 29 ], Enteritidis [ 22 , 30 ], Heidelberg [ 31 ], Manhattan [ 21 ], Montevideo [ 32 , 33 ], and Typhimurium [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis based on WGS-derived SNPs has been shown to provide greater cluster resolution than the gold standard subtyping method, pulsed-field gel electrophoresis (PFGE), resulting in discrimination of outbreak-related human clinical isolates and food or environmental origins [ 21 23 ]. ParSNP was run for all the 200 Salmonella genomes and separately for each of the serovars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the outbreak must be taken into account when defining a single outbreak, given that many parameters are possibly affecting the results (e.g., the genetic makeup of the serovar, routes of infection, source types, and time). The SNP analysis and other WGS methods for typing provide a higher discrimination of isolates in comparison with other conventional typing methods ( 12 19 ) and gives the advantage of many additional analyses. However, new typing approaches also lead to many new questions on how to interpret data and, in a surveillance context, how to define outbreak cases and sources.…”
Section: Discussionmentioning
confidence: 99%
“…The vast amount of data provided by this method not only enables high-resolution typing for surveillance but also provides valuable additional data regarding further characterization of emerging clones based on genetic differences and evolutionary studies. Several studies have proven WGS-based typing to have an enhanced discriminatory power in comparison to current molecular typing methods used for Salmonella ( 12 19 ), although few studies have evaluated WGS analysis in real-time surveillance. A retrospective study of Salmonella Enteritidis showed that single-nucleotide polymorphism (SNP)–based WGS analysis was suitable for surveillance purposes ( 15 ).…”
mentioning
confidence: 99%